2015
DOI: 10.1097/aog.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Time Interval Between Endometrial Biopsy and Surgical Staging for Type I Endometrial Cancer

Abstract: Wait time for surgical staging was not associated with decreased survival outcome in patients with type I endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…When evaluating the safety of fertility preservation in patients with presumed grade 1 EC confined to the endometrium, the risk of subestimation of the tumor stage was not associated with increased mortality. 23 Interestingly, Matsuo et al 24 showed that the wait time for surgical staging was not associated with decreased survival outcome in patients with a low-grade EC. On the contrary, in patients with presumed stage I, grade 2 or 3 EC, the probability of underestimating the grade and/or stage of cancer is increased.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the safety of fertility preservation in patients with presumed grade 1 EC confined to the endometrium, the risk of subestimation of the tumor stage was not associated with increased mortality. 23 Interestingly, Matsuo et al 24 showed that the wait time for surgical staging was not associated with decreased survival outcome in patients with a low-grade EC. On the contrary, in patients with presumed stage I, grade 2 or 3 EC, the probability of underestimating the grade and/or stage of cancer is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Our agreement rate of 64.2% is consistent with that reported in most previous studies (63.3%Y71.1%). 11,12,14,17,19 In Table 6, there is a summary of results from previous studies on the subject. As in these previous investigations, the highest accuracy in our study was found among G3 lesions, 78.9% of biopsies graded as G3 were accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Given that our study population was predominantly obese study did not answer if the tumors progressed from endometrial hyperplasia to carcinoma in the time interval between endometrial biopsy and hysterectomy. However, biopsy-tohysterectomy time interval was not associated with concurrent carcinoma (median time, 3.5 months), and type I endometrial cancer generally progresses slowly [9]. Therefore, it is likely that carcinoma had co-existed with hyperplasia at the time of endometrial hyperplasia diagnosis.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The STROBE guidelines were consulted for reporting in a case-control study [6]. Some cases of the study population were within the context of our previous studies [7][8][9][10][11].…”
Section: Eligibilitymentioning
confidence: 99%